Form and Function of the Mo Manggoba Gua Mantra in Buol Society - Moh. Iqbal A. Haruna; Muslimin; Herman Didipu (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Mantra is a genre of oral literature in the form of a language composition imbued with belief in the supernatural and sacred world. Mo Manggoba Gua is a type of mantra used by the Buol people, in the form of recitations carried out when planting dryland rice. This study aims to describe: (1) The form of the mo manggoba gua mantra, (2) The function of the mo manggoba gua mantra. The method used in this study is a qualitative descriptive method. The research data are the mo manggoba gua mantra obtained from interviews with informants in Paleleh District, Buol Regency. The research data were collected through: (1) documentation, (2) interviews, (3) recording techniques, (4) note-taking techniques. Data analysis techniques include the following stages: (1) data reduction, (2) data presentation, (3) drawing conclusions and verification. The results of the study show 39 verses of the mo manggoba gua mantra classified into three types: farming mantra, maintenance and pest and disease control mantra, and harvest mantra. The entire data of the mo manggoba gua mantra is pure oral literature in the form of free poetry. Meanwhile, the mo manggoba gua mantra has four functions, namely: (1) as a projective function, (2) as a function of ratifying cultural institutions and institutions, (3) as an educational function, (4) as a social control function. Based on these results, it can be concluded that the mo manggoba gua mantra is an oral tradition that has an important role in the lives of the Buol people, both from an aesthetic, educational, cultural, and social aspect.